Nearly three in every five prisoners experience common mental disorders (CMDs) in Jimma correctional institution; south-West Ethiopia - Wasihun Adraro; Habtamu Kerebih; Workinesh Tesema; Fira Abamecha; Hailemariam Hailesilassie (BMC, 2019)
Abstract Background Millions of people are currently suffering from some form of mental disorders. The prevalence of common disorders is twofold higher in prison than general population and the condition is found to be worst in African in general and Ethiopia in particular. The aim of this study was to assess the prevalence of common mental disorders and its correlates among prisoners in Jimma town correctional institution; Ethiopia. Methods A cross sectional quantitative study was conducted enrolling 300 prisoners. The participants were recruited using systematic random sampling technique. The World health organization Self Reporting Questionnaire (SRQ-20) scale; was adapted to assess prevalence of mental disorders. Data were collected on interviewer administered basis by trained personnel. Statistical package for social sciences (SPSS) version 20 for widows was used for data analysis. Multivariate logistic regression modelling was conducted to identify the independent predictors of common mental disorders. P-value less than 5% was considered to indicate significant associations. Results The prevalence of common mental disorder was found to be 62.70, 95% CI; [57.30, 68.50]. Prisoners who had monthly income of 1500-3000birr, AOR = 3.30, 95% CI; [1.25, 8.69] and above 3000birr; AOR = 4.75, 95% CI; [1.57, 14.33], family history of mental illness; AOR = 6.14, 95% CI; [1.65, 22.79] and who ever used Khat; AOR = 4.33, 95% CI; [2.02, 9.27] were more likely to experience common mental disorders. Conversely; having some sort of work in prison; AOR = 0.25, 95% CI; [0.12, 0.54], perceived moderate social support; AOR = 0.094, 95% CI; [0.04-0.215] and perceived moderate strong; AOR = 0.025, 95% CI; [0.009, 0.07] were found to be protective factors. Conclusion Prevalence of common mental disorder was considerably high as nearly more than three in every five prisoner experience some form of the disorder. Early screening of prisoners up on their arrival, appropriate treatment and follow up should be done. Furthermore; creating prison based jobs that could bring prisoners together and encouraging positive relationships to build social supports as coping strategy is required.